Whispering Game to Improve Students’ Listening Skill - Safira Jaefatul Alfiah; Eny Maulita Purnama Sari; Aulfa Reyza Ayuni Prestika (Journal of English Development, 2026)
This study aims to explain the use of whispering game in improving students’ listening skills at eight-gradestudents of MTs Ma'arif NU 21 Buana Sakti. This study involved one class consisting of 18 students from MTs Ma'arif NU 21 Buana Sakti. This study was conducted using the Classroom Action Research (CAR) method, which was carried out in two cycles. Data collection was carried out through observation, tests, and documentation. Then, the data analysis technique used in this study was qualitative and quantitative descriptive analysis. In cycle I, students showed an activity score of 35% and post-test I score of 33,33% with an average score of 57,22 from 18 students. However, cycle II showed a significant improvement, with student activity scores increasing to 74% and post-test II scores of 77,77% with an average score of 70, indicating that the students met the success criteria. The findings indicate that the Whispering Game is an effective medium for improving students' listening skill and is recommended for use in English language teaching.